口腔毛状白板症とEBV陽性粘膜皮膚潰瘍を併発したリウマチ患者の1例 - 長尾, 徹; 大隅, 縁里子; 齊藤, 輝海; 大林, 修文; 伊藤, 洋平; 柏原, 捷 (日本口腔外科学会雑誌, 2021)
Oral hairy leukoplakia has been regarded as a lesion characteristic of human immunodeficiency virus (HIV) infection; however, many cases are reported in HIV-negative immunocompromised patients. A EBV-positive mucocutaneous ulcer was first reported by Dojcinov et al. in 2010 and was categorized as an EBV-associated lymphoproliferative disorder. The cause is EB virus reinfection associated with iatrogenic or age-related immunosuppression. We report a case in which OHL and EBVMCU coexisted. The case involved a 75-year-old woman who visited our department for the purpose of examining a white lesion on the right tongue margin. A smooth, thin, uniform white lesion with a shallow, flat, well-defined, painful ulcer was found on the right lingual margin. She had a medical history of rheumatoid arthritis, which was treated with oral methotrexate therapy. The white lesion was accompanied by an ulcer. We suspected leukoplakia, intractable ulcer, and methotrexate-related lymphoproliferative disorder (MTX-LPD), and performed a biopsy of her tongue. Results confirmed that the lesions were overlapped with the oral hairy leukoplakia and EBV-positive mucocutaneous ulcer. We considered iatrogenic immunosuppression as the cause, and methotrexate treatment was discontinued. The ulcer healed 4 weeks after methotrexate was discontinued, and the hairy leukoplakia thinned.